2022
DOI: 10.3389/fnins.2022.1039977
|View full text |Cite
|
Sign up to set email alerts
|

Maternal melatonin treatment rescues endocrine, inflammatory, and transcriptional deregulation in the adult rat female offspring from gestational chronodisruption

Abstract: IntroductionGestational chronodisruption impact maternal circadian rhythms, inhibiting the nocturnal increase of melatonin, a critical hormone that contributes to maternal changes adaptation, entrains circadian rhythms, and prepares the fetus for birth and successful health in adulthood. In rats, we know that gestational chronodisruption by maternal chronic photoperiod shifting (CPS) impaired maternal melatonin levels and resulted in long-term metabolic and cardiovascular effects in adult male offspring. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…As well, gestational chronodisruption impact fetal hormonal rhythms like prolactin, corticosterone and melatonin 4,65,67 . Collectively these results support that fetal physiology was impacted by melatonin suppression since we and others have demonstrated that maternal melatonin treatment reversed this effect in the fetus restoring normal fetal physiology 18,42,67,77,83 . Moreover, the work of our group and others has widely demonstrated that melatonin signals impact the molecular clockwork of several brain and peripheral regions in fetuses from a number of species in which melatonin receptors are expressed (reviewed in 1,18,53,67,80,87 ), similar to those reported in adults (Table 1).…”
Section: Impact Of Gestational Chronodisruption On Maternal‐fetal Healthsupporting
confidence: 71%
See 2 more Smart Citations
“…As well, gestational chronodisruption impact fetal hormonal rhythms like prolactin, corticosterone and melatonin 4,65,67 . Collectively these results support that fetal physiology was impacted by melatonin suppression since we and others have demonstrated that maternal melatonin treatment reversed this effect in the fetus restoring normal fetal physiology 18,42,67,77,83 . Moreover, the work of our group and others has widely demonstrated that melatonin signals impact the molecular clockwork of several brain and peripheral regions in fetuses from a number of species in which melatonin receptors are expressed (reviewed in 1,18,53,67,80,87 ), similar to those reported in adults (Table 1).…”
Section: Impact Of Gestational Chronodisruption On Maternal‐fetal Healthsupporting
confidence: 71%
“…As adults, the offspring gestated under chronodisruption, display multiple physiological changes including increased heart rate, blood pressure, body weight, and glucose tolerance, among others (see Table 1). In this context it is important to keep in mind that the effects on the offspring of gestational chronodisruption have been studied experimentally in several species using models, such as maternal pinealectomy, 83,92–94 maternal exposure to constant light 67,78–80,84,85,95 and maternal exposure to chronic phase shifts during gestation, 20,21,23,76,77,96 that display in common the alteration or suppression of the maternal circadian rhythm of melatonin, shifting maternal circadian rhythms of glucose, and suppressing the maternal rhythms of activity, temperature, and heart rate. In these models has been demonstrated that the impairment in fetal organs at circadian and physiological levels are translated to the offspring inducing metabolic impairment, with higher response to intraperitoneal glucose challenge, increasing adrenal response to adrenocorticotropic hormone in vitro, free‐running of corticosterone and permanent effects in plasma melatonin, that remain for the whole life, in which the nocturnal increase of melatonin was absent (Table 1).…”
Section: Long‐term Consequences Of Gestational Chronodisruption On Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there have been several animal studies reporting that melatonin exogenous supplementation during gestation could be beneficial for both mother and fetus [62], while only a small proportion of them have focused on offspring outcomes [55]. Here, we list in Table 1 a summary of reports relevant to reprogramming effects of melatonin on kidneyrelated diseases in offspring [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The therapeutic duration is restricted solely to fetal to early childhood stages prior to disease onset.…”
Section: Melatonin Use For the Early Origins Of Kidney Diseases In An...mentioning
confidence: 99%
“…Table 1 illustrates various maternal insults that can induce the developmental programming of kidney-related disease in adult offspring, which can be averted by the early use of melatonin. These early life insults include gestational chronodisruption [63], maternal continuous light exposure [65], maternal caloric restriction [66], maternal N G -nitro-L-argininemethyl ester (L-NAME) exposure [67], maternal high methyl-donor diet [68], maternal high-fructose diet [69], maternal high-fructose diet plus post-weaning high-salt diet [70], antenatal glucocorticoid exposure [71], and antenatal glucocorticoid administration plus post-weaning high-fat diet [72].…”
Section: Melatonin Use For the Early Origins Of Kidney Diseases In An...mentioning
confidence: 99%